Social Robots and Storytelling: Evaluating Inclusion and Student Engagement through Robotics and the Interactive Whiteboard - Rossi, Lino; Orsenigo, Enrico; Pellizzari, Cecilia; Valentini, Maria (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2024)
<div class="min-h-[20px] text-message flex w-full flex-col items-end gap-2 whitespace-pre-wrap break-words [.text-message+&]:mt-5 overflow-x-auto" dir="auto" data-message-author-role="assistant" data-message-id="4d6477c2-08b5-44e1-96c8-e38a99db7695"> Anthropomorphic robots are becoming increasingly common in educational settings, enhancing language skills and supporting students' learning and emotional development. Despite their potential, research on how these robots influence learning is still limited. The National Association for the Education of Young Children (NAEYC) has highlighted the need to better understand the use of technology in education. Social robots, with features such as voice and facial recognition, are perceived by children as learning companions, significantly improving educational outcomes, particularly in language acquisition. Our study explores a new balance between cognitive and affective aspects in the use of educational robotic technologies, developing in three phases: intervention design, storytelling with an illustrated book accompanied by playful activities, and qualitative evaluation of student engagement using Interactive Whiteboards (IWBs) and educational robotics (M bot 2). This article is the first in a series that will present the results of observation grids; subsequent articles will follow with qualitative analysis of data collected through focus groups. The research is interdisciplinary, encompassing themes such as collaborative education, educational storytelling, and the use of technologies to intuitively and engagingly mediate educational content.